Conflict Resolution of Political Parties in The Coalition Nominating Presidential/Vice Presidential Candidates in Indonesia in 2024 - Unggul Sugi Harto; Diniyanto, Ayon; Baqil, Youssef; Death, Carl H; Muyassaroh, Inas Sany (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2026)
This research investigates the friction and subsequent settlement strategies within party alliances during the 2024 Indonesian presidential election. By examining high-level negotiations and the shifting landscape of candidate nominations, the study interprets these dynamics as essential conflict management within a multiparty framework. Using a qualitative lens, the author analyzed digital media reports through thematic coding to pinpoint how alliances were formed, broken, and rebuilt. The analysis reveals that tension primarily stemmed from a